2018
DOI: 10.1055/s-0038-1670652
|View full text |Cite
|
Sign up to set email alerts
|

Ahead of the Curve: Tracking Progress in Novice Microsurgeons

Abstract: Background The purpose of this study was to evaluate learning curves for an existing microsurgical training model. We compared efficiency and amount of training needed to achieve proficiency between novice microsurgeons without operative experience versus those who had completed a surgical internship. Methods Ten novice microsurgeons anastomosed a silastic tube model. Time to perform each anastomosis, luminal diameter, and number of errors were recorded. Results First year residents imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Another example is the ex vivo ovine model for microsurgical training on parotidectomy and facial nerve reanimation [67]. Persistent, repeated, interval [68], deliberate, self-directed practice on low-fidelity platforms are excellent alternatives to high-fidelity models [69][70][71]. It is found that having previous practical experience with ex vivo models enhances skill retention [70,72], confidence [73], and cognitive perception within the operating room because the technical skills have been mastered and become automatic.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is the ex vivo ovine model for microsurgical training on parotidectomy and facial nerve reanimation [67]. Persistent, repeated, interval [68], deliberate, self-directed practice on low-fidelity platforms are excellent alternatives to high-fidelity models [69][70][71]. It is found that having previous practical experience with ex vivo models enhances skill retention [70,72], confidence [73], and cognitive perception within the operating room because the technical skills have been mastered and become automatic.…”
Section: Discussionmentioning
confidence: 99%
“…The learning curve in microsurgery is steep and has been extensively researched. 24 To account for this, every effort was made to compare same-experienced trainees for comparison within each cohort and across cohorts. That being said, we acknowledge intercohort variability may have contributed to the disparate results across both cohorts.…”
Section: Limitationsmentioning
confidence: 99%
“…This allows the students to reflect on their mistakes and remediate any failed or unsuccessful attempts. 24 From a pedagogical point of view, students build a relationship with their instructor. The interaction between student and instructor is invaluable; it helps students develop resilience, patience, and confidence toward accomplishing their task.…”
Section: Limitationsmentioning
confidence: 99%
“…Another synthetic model described in the literature for microsurgery skills training is the “Japanese noodle model” which has shown close resemblance to the rat's femoral artery owing to the same diameter (Prunières et al, ). Brosious et al () described the use of silastic tubes to simulate blood vessels in order to learn microsurgical anastomosis. Hoşnuter et al () introduced the concept of polyethylene stretch film membrane to simulate adventitial stripping, thereby improving silicone model's fidelity.…”
Section: Bench Modelsmentioning
confidence: 99%